Navigating Bipolar Parenthood: Understanding the Bio-Psychosocial Impact on Children - An In-depth Exploration through Interpretative Phenomenological Analysis in Pakistan - Iqbal, Naveed; Riaz, Samina; Bukhari, Sara; Muazzam, Amina (Pakistan Journal of Humanities and Social Sciences, 2024)
This study is an attempt to explore the complex problems faced by children of bipolar disorder diagnosed parents in Pakistan. By employing qualitative approach, it was aimed to gain a deeper understanding of psycho, social and biological aspects of wellbeing of such children. Interpretative analysis of in-depth interviews of participants was carried out for exploring uniqueness of their experiences Through purposive sampling a sample of five individuals between the ages of 15-20 years was selected, and in-depth, semi-structured interviews were conducted for of data collection. Analysis of interviews showed that effects of bipolar disorder on children go beyond just psychological, social, and biological impacts. This research emphasized the significant effects of gender and birth in shaping their experiences. It was also found that diagnosis of bipolar disorder does not only affects patient but it also influences their families. This accentuates the need for comprehensive interventions and support that identifies the complex dynamics within the family unit.